Terapkan Perilaku “CERDIK” untuk Hidup Sehat & Bebas dari Penyakit Kardiovaskular - Arrang, Sherly Tandi; Jerrycho, Jerrycho; Then, Julia; Suhanto, Jessica; Nidya, Joyce; Benneditha, Lasmaria; Sianipar, Erlia Anggrainy (Poltekita: Jurnal Pengabdian Masyarakat, 2024)
Cardiovascular disease is the main cause of death throughout the world. Prevention of cardiovascular disease can reduce mortality rate. Some of the main risk factors for cardiovascular disease in office employees are smoking habits, lack of physical activity, unbalanced diet, obesity, high blood pressure, diabetes, stress and lack of sleep. Considering the importance of changing people's behavior to be more aware of risk factors that lead to cardiovascular disease, education and health checks are carried out targeting office employees. Health promotion programs can reduce the risk of disease in company employees. Educational activities “CERDIK” and blood pressure and cholesterol checks were carried out at one of the accounting offices in North Jakarta. The number of participants who took part in this activity was 87 people. Participants with a good level of knowledge before education were 71.9% and after education 96.9%. The majority of participants had abnormal cholesterol levels (36.8%) and blood pressure in the pre-hypertension (40.2%) and grade 1 hypertension (36.8%) categories. Respondents need to have regular medical check-up because most of them have risk factors for cardiovascular disease, and implement "CERDIK" behavior. Examination of LDL, HDL, glucose levels, measurements body weight and body height, should also be carried out to calculated the risk level of cardiovascular disease. The Company plans to carry out routine medical check-up for employees.